Evaluasi Profil Sensori Sediaan Pemanis Komersial Menggunakan Metode Check-All-That-Apply (CATA) - Dede Robiatul Adawiyah; Kariska Iswari Yasa (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2017)
Table-top sweetener is sweeteners in the form of granule, powder, tablet or liquid ready to be consumed as final product are packed in disposable packaging. CATA is a simple and valid tools for gathering information about food products based on consumer perception. There were two steps in CATA method: a panelist selection part and a sensory testing part. The objective of this study were to (1) profiled sensory characteristics of ideal sweetener and commercial table-top sweeteners by non-diabetic and diabetic panelists, (2) identified the panelist preferences mapping for commercial table-top sweeteners, and (3) identified the potential sensory attributes in table-top sweetener development. CATA analysis results with XLSTAT 2016 software indicates that perception ideal sweeteners by non-diabetic panelists have a sensory profile that sweet, sweet aftertaste, body and cooling. A, B, and D come closest to the ideal sweetener. Meanwhile perception ideal sweetener by diabetic panelists have a sensory profile that sweet and body. D come closest to ideal sweetener. D is the most favored product by non-diabetic and diabetic panelists, because D get a preference value above the average from all panelists. There is no correlation between the sensory attributes and panelist preference that significant at 5% sign level, it means that there is no table-top sweetener sensory attributes that control panelist preference significantly. In product development, table-top sweeteners for non-diabetic consumer must not have a bitter aftertaste and nice to have a sweet aftertaste. Meanwhile table top sweeteners for diabetic consumer must have a body attribute but not significant at 5% test level.